1986
DOI: 10.1111/j.1469-7610.1986.tb01835.x
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Disorder With Hyperactivity: A Critique

Abstract: The DSM III category of Attention Deficit Disorder with Hyperactivity is considered within a framework of Rutter's (1977) outline of criteria for adequacy of psychiatry classification. Discussion of problems with the operationalization and definition of 'attention deficit' and the difficulty of using this rubric in distinguishing between ADDH and other related childhood disorders, along with the consequent failure to meet other important criteria, leads to the conclusion that the concept needs re-appraisal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 81 publications
3
31
1
1
Order By: Relevance
“…Some theorists have suggested that ADHD is an epiphenomenon associated with a variety of diagnoses including CD (Prior & Sanson, 1986). However, factor analyses have demonstrated that ADHD and CD are separate, though highly correlated, factors in clinical populations (Fergusson, Horwood, & Lloyd, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Some theorists have suggested that ADHD is an epiphenomenon associated with a variety of diagnoses including CD (Prior & Sanson, 1986). However, factor analyses have demonstrated that ADHD and CD are separate, though highly correlated, factors in clinical populations (Fergusson, Horwood, & Lloyd, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several authors have suggested to define these instances of hyperactivity in terms of two classes of behavior: Inattention and Overactivity (Donnelly & Rapoport, 1985;Prior & Sanson, 1986). The behaviors that were considered within each class in this study are listed in Table I.…”
Section: Definition Of Target Behaviorsmentioning
confidence: 99%
“…Hyperactivity and conduct disorder have been closely linked in a variety of ways (Prior & Sanson, 1986;Quay, 1985). In the present study, two children displayed conduct disorders in baseline; a decrease in the frequency of such disorders was reported during treatment.…”
Section: Correspondence Training and Hyperactivity/lsmentioning
confidence: 99%
“…Hyperactive children exhibit disabling learning and behavioural problems, pose great difficulties for their families and teachers, and are at risk for social and behavioural disturbances in adolescence and adulthood (Weiss & Hechtman, 1986). Despite much research, however, it is not clear whether hyperactivity is a valid diagnostic entity with characteristics that distinguish it from other psychopathological disorders of childhood Prior & Sanson, 1986). Efforts to define it continue on several fronts, including the broad category of family studies.…”
Section: Introductionmentioning
confidence: 99%